The Prevalence of Online Gaming Addiction Among Senior High School Students - Yuda Gumelar; Linda Faulani; Heni Purnama (LPPM UNIKAL, 2025)
Background: Online games have become one of the most popular forms of entertainment among adolescents, offering social and emotional engagement. However, excessive gaming can lead to addiction, especially during the developmental stage of adolescence. Objective: This study aims to examine the prevalence of online game addiction among senior high school students. Methods: This research employed a descriptive quantitative method with a cross-sectional design. The population included all students in grades X and XI at Government Senior High School 1 Kertasari during the 2024–2025 academic year. A total sampling technique was used, involving 452 students who actively play online games. Data were collected using the POGQ (Problematic Online Gaming Questionnaire). Results: The majority of respondents were male (62.8%) with an average age of 17 years. Most played Mobile Legends (66.7%), used smartphones as their primary gaming device (97.6%), had been playing online games for ≥ 3 months (88.5%), played for ≤ 3 hours per session (65.5%), and played games daily (93.1%). Regarding addiction levels, 57.3% were categorized as moderate, 42.5% as high, and only 0.2% as low. The domain with the highest average score was social interaction (M = 10.78, SD = 2.064), indicating that peer engagement and the need for social connection play a significant role in adolescents’ gaming behaviours. Conclusion: The majority of students exhibited a moderate level of online game addiction, indicating a pattern of frequent gaming driven by psychological and social needs, particularly the desire for peer interaction and acceptance. Recommendations: Schools, parents, and mental health professionals should collaborate in developing structured interventions and providing healthy social alternatives to help adolescents achieve a balanced lifestyle and prevent gaming-related problems.